Insights Into the Evolution of the prdm1/Blimp1 Gene Family in Teleost Fish - Perdiguero, Pedro; Goméz-Esparza, Maria C.; Martín, Diana; Bird, Steve; Soleto, Irene; Morel, Esther; Díaz-Rosales, Patricia; Tafalla, Carolina (Frontiers in Immunology, 2020)
In mammals, Blimp1 (B lymphocyte-induced maturation protein 1) encoded by the prdm1 gene and its homolog Hobit (homolog of Blimp1 in T cells) encoded by znf683, represent key transcriptional factors that control the development and differentiation of both B and T cells. Despite their essential role in the regulation of acquired immunity, this gene family has been largely unexplored in teleosts to date. Until now, one prdm1 gene has been identified in most teleost species, whereas a znf683 homolog has not yet been reported in any of these species. Focusing our analysis on rainbow trout (Oncorhynchus mykiss), an in silico identification and characterization of prdm1-like genes has been undertaken, confirming that prdm1 and znf683 evolved from a common ancestor gene, acquiring three gene copies after the teleost-specific whole genome duplication event (WGD) and six genes after the salmonid-specific WGD. Additional transcriptional studies to study how each of these genes are regulated in homeostasis, in response to a viral infection or in B cells in different differentiation stages, provide novel insights as to how this gene family evolved and how their encoded products might be implicated in the lymphocyte differentiation process in teleosts.